Evaluation of Cultivated and Wild Brinjal Germplasm against Bacterial Wilt Disease with Tollinterleukin-1 Receptors (TIR)-NBS-LRR Type R-gene Specific Degenerate Primer - Hansda, S.; Jamir, I.; Pramanik, K.; Banerjee, J.; Chattopadhyay, A.; Mandal, A. K. (International Journal of Bio-resource and Stress Management, 2021)
The experiment was conducted at C-Block Farm of Bidhan Chandra Krishi Viswavidyalaya, Kalyani, West Bengal, India during 2017–18 to screen eight brinjal germplasm lines against BW disease using tollinterleukin-1 receptors (TIR)-NBS-LRR type R-gene specific degenerate primer. The study showed that wild genotype S. torvum was highly resistant to bacterial wilt incidence with no wilting symptom whereas two cultivated genotypes (Utkal Anushree and Utkal Madhuri) and one wild genotype S. sisymbriifolium were found to be resistant to BW disease. Out of the 7 germplasm sequences, 2 had no match with R-genes whereas the remaining 5 sequences have 70-93% homology with R-genes of other plant species submitted in Gene Bank sequence database. Nearly 90% sequence identity of brinjal NBS-LRR RGA was found by analyzing through BLASTn with NBS-LRR RGAs of other solanaceous crops. Two cultivated resistant genotypes (Utkal Madhuri and Utkal Tarini) were similar to the wild resistant type S. sisymbriifloium, while cultivable resistant genotype Utkal Anushree was highly different at sequence level. Two cultivable susceptible genotypes (BCB-30 and Garia) showed high level of similarity among them and they were strongly associated with the wild susceptible genotype S. macrocarpum. Two cultivable genotypes Utkal Anushree and Utkal Madhuri could be utilized in future breeding programme and two wild genotypes S. torvum and S. sisymbriifolium could be used as resistant rootstocks in brinjal grafting.